Tibet : travel survival kit / Chris Taylor - Chris Taylor
This is the 3rd edition guide book to travel Tibet, one of the most remarkable places to visit in Asia: it is also a country under occupation. It offers fabulous monastery sights, taxing high-altitude treks, stunning iews of the world's highest mountains and fabled pigrimage routes. But you are never far from the reality of politics. For anyone who travels with their eyes open, a visit to Tibet will be a memorable, fascinating, but sometimes disturbing experience.